Facile Synthesis of Silver Nanoparticles of Aqueous Extract of Bhut Jolokia a Cultivar of Capsicum chinense Jaqc and its Antibacterial Effect - Vijayaraghavan ,; Shahnaj Hussain Mazumder, (Journal of Basic & Applied Sciences, 2019)
The article explores a novel method of synthesizing silver nanoparticle using aqueous extract of Capsicum chinense Jaqc. The capsaicinoid alkaloids and polyphenols served as an reducing and stabilizing agent in the formation silver nanoparticles. The formation of silver nanoparticle was confirmed by the surface Plasmon resonance which occurred at 430 nm. A gradual colour change of the reaction medium occurred from colourless to pale yellow tinge followed by pale red and then to intense reddish brown colour. The completion of nanoparticle synthesis occurred at 6 hr, as further increased in reaction time showed a marginal rise in the intensity of colour. The characterization of the formed silver nanoparticle was carried out using UV Visible Spectrophotometry and Transmission Electron microscopy. The antibacterial studies were carried out using well diffusion technique using pure culture of Escherichia coli, which showed an inhibition zone of 11.8 mm at a dosage of 70 μg/ml.